Culture of Kenyan Goat (Capra hircus) Undifferentiated Spermatogonia in Feeder-Free Conditions - Nabulindo, Nakami Wilkister; Nguhiu-Mwangi, James; Kipyegon, Ambrose Ng'eno; Ogugo, Moses; Muteti, Charity; Christian, Tiambo; Oatley, Melissa J.; Oatley, Jon M.; Kemp, Stephen (Frontiers in Veterinary Science, 2022)
The undifferentiated spermatogonial population in mammalian testes contains a spermatogenic stem cell (SSC) population that can regenerate continual spermatogenesis following transplantation. This capacity has the potential to be exploited as a surrogate sires breeding tool to achieve widespread dissemination of desirable genetics in livestock production. Because SSCs are relatively rare in testicular tissue, the ability to expand a population in vitro would be advantageous to provide large numbers for transplantation into surrogate recipient males. Here, we evaluated conditions that would support long-term in vitro maintenance of undifferentiated spermatogonia from a goat breed that is endemic to Kenyan livestock production. Single-cell suspensions enriched for undifferentiated spermatogonia from prepubertal bucks were seeded on laminin-coated tissue culture plates and maintained in Stempro serum-free medium that had been conditioned by goat fetal fibroblasts and supplemented with a growth factor cocktail that included GDNF, LIF, SDF, and FGF. Over a 45-day period, the primary cultures developed a cluster morphology indicative of in vitro grown undifferentiated spermatogonia from other species and expressed the tell-tale germ cell marker VASA as well as the previously defined spermatogonial marker PLZF. Taken together, these findings provide a methodology for isolating the SSC containing undifferentiated spermatogonial population from goat testes and long-term maintenance in defined culture conditions.